Evaluating the contamination level of total petroleum hydrocarbons (TPHs) and heavy metals in coastal sediments of Tiab Mangroves (Hormozgan Province) - Liela Zahedi Dehuii; Afshin Qishlaqi; Mohammad Seddiq Mortazawi (Journal of Stratigraphy and Sedimentology Researches, 2019)
Abstract In order to evaluate the contamination degree of sediments in Tiab mangroves (Hormozgan province) in terms of Total Petroleum Hydrocarbons (TPH) and heavy metals concentration, 16 sediment samples were collected from the study area. In addition to TPH and metal concentrations, physicochemical properties of sediments such as grain size, pH, total organic matter and organic carbon were measured using the standard methods. The concentrations of heavy metals and concentration of total petroleum hydrocarbons was determined. Petroleum hydrocarbons in sediments narrowly varied from 0.36 to 4.89 (µg/g). The highest TPHs concentrations are found in sediments from Tiab and Kolahi berth probably due to inputs from coastal anthropogenic activities. Using sediment quality guidelines and the contamination factor, it was found that there is no adverse biological effect in terms of TPH concentration. It was also revealed that metal concentrations in sediments ranged from 163 mg/kg for Ni to 8 mg/kg for Pb and their mean concentrations are all higher than the corresponding concentrations in the Persian Gulf sediments. Calculated enrichment factor showed that all metals (except for Ni) have low contamination level. However, the overall ecological risk is found to be moderate (78.14) for all studied metals. The results of cluster and correlation analyses showed that most metals (Pb, Zn, Cr) are originated from natural source while total petroleum hydrocarbons alongside Ni and V were most likely derived from anthropogenic sources.